LAPAROSCOPIC EVALUATION OF FEMALE INFERTILITY - Haider, Gulfareen; Rani, Shazia; Talpur, Sabreena; Zehra, Nishat; Munir, Aftab (Journal of Ayub Medical College Abbottabad, 2010)
Background: Sub-fertility is inability to ensure child bearing when it is wanted. Prevalence of sub-fertility in industrialised countries has been quoted as 20%, and seems to be on the rise. Traditional way to assess the uterine cavity, tubal structure and tubal patency was hysterosalpingography but it has now been largely superseded by laparoscopy and hysteroscopy. The objective of this study was to highlight the role of laparoscopy in establishing diagnosis of female infertility. Methods: This descriptive study was conducted in Gynaecology Unit of Liaquat University of Medical Health Sciences, Hyderabad, Pakistan from 28th August 2000 to 1st July 2001. Total 200 sub-fertile patients attended the gynaecology OPD. Out of these 30 patients were selected for laparoscopy and dye test who were suspected cases of endometriosis, abnormal HSG and unexplained infertility. Those patients who had medical disorders and contraindication for laparoscopy were excluded from study. Detailed history of every patient was recorded on a proforma and physical examination was performed. Laparoscopy was scheduled in proliferative phase of menstrual cycle. Data were analysed using SPSS 11. Frequency and percentages were calculated to describe the results. Results: Out of 200 sub-fertile patients total 30 patients were selected for laparoscopy. Twenty (66%) patients were in primary infertility group while 10 (33%) patients were in secondary infertility group. Eleven (55%) patients of primary infertility belong to age group of 18-25 years while 6(60%) patients of secondary infertility belong to age group of 26- 33 years (TABLE 1). Mean duration of sub fertility at time of presentation in primary infertility group was 1.95 years while in secondary infertility was 2.70 years (Table 2). In primary infertility group main associated symptoms were dysmenorrhoeal in 8 (40%), irregular cycles 5 (25%), and dyspareunia in 4 (20%). In secondary infertility group 3 (30%) patients had dysmenorrhoeal and dyspareunia while 2 (20%) had irregular cycles. The commonest cause observed in patients with primary infertility was endometriosis spots which accounted for 11 (55%). In secondary infertility tubal occlusion was more common which accounted for 3 (30%). Conclusion: Laparoscopic procedures are less invasive, more convenient and more precise for diagnosis of sub-fertility in women. Keywords: Laparoscopy, Primary infertility, Secondary infertility, Complications